Engineering of high-performance textiles - Miao, Menghe; Xin, John H. (Textile Institute book series., 2018)
Engineering of High-Performance Textiles discusses the fiber-to-fabric engineering of various textile products. Each chapter focuses on practical guidelines and approaches for common issues in textile research and development. The book discusses high-performance fibers and yarns before presenting the engineering fabrics and architectures needed for particular properties required of high-performance textiles. Properties covered include moisture absorption, pilling resistant knitwear, fire retardant fabrics, camouflage fabrics, insect repellent fabrics, filtration, and many more. Coordinated by two highly distinguished editors, this book is a practical resource for all those engaged in textile research, development and production, for both traditional and new-generation textile products, and for academics involved in research into textile science and technology. Offers a range of perspectives on high-performance textiles from an international team of authors with diverse expertise in academic research, textile development and manufactureProvides systematic and comprehensive coverage of the topic from fabric construction, through product development, to the range of current and potential applications that exploit high-performance textile technologyLed by two high-profile editors with many years' experience in engineering high-performance textiles.